Transforming Early Childhood Care and Education in Manipur through Art and Play-based Pedagogies under NEP 2020 and NCF-FS 2022 - Meitei, Akoijam Pete; Singh, Naorem Ingochouba; Singh, KH. Kesho (JOURNAL OF INDIAN EDUCATION, 2026)
The article discusses integrating art and play-based pedagogies into early childhood care and education in Manipur. It focuses on three key developmental goals: maintaining health and well-being, becoming effective communicators, and evolving as involved learners connected to their surroundings. Using a qualitative methodology and thematic analysis, the study analyses policy frameworks, academic literature, and best global practices to evaluate the alignment of these pedagogical approaches with the objectives of NEP 2020 and NCF-FS 2022. It emphasises the importance of art and play in early childhood development, outlining different types of play and their benefits. The paper provides strategies for implementing these approaches to support physical health, motor skills, mental well-being, language development, multilingual exposure, and experiential learning. Despite challenges like resource constraints and teacher training, the article highlights the new policy framework’s opportunities. It concludes with recommendations for future directions, including research, technology integration, community engagement, and continuous professional development. The paper examines how integrating art and play-based pedagogies is crucial for achieving holistic development in young children and realising India’s vision for high-quality early childhood education.